New records of the rare Troschel’s Pampas Snake, Phimophis guianensis (Serpentes: Dipsadidae) in Brazil - ENTIAUSPE-NETO,OMAR M. (2018)
Abstract The Troschel’s Pampas Snake, Phimophis guianensis (Troschel, 1848), is widely distributed in Amazonian Savannas at northern South America and a small portion of southern Central America, being recorded to Brazil based on three historical records, that ranged from 1997 to 2002, in Amapá and Pará states. In this study, we revise all known records of P. guianensis, providing an updated distribution map, and the first record to Roraima state.